Bacteriological spectrum, extended-spectrum β-lactamase production and antimicrobial resistance pattern among patients with bloodstream infection in Addis Ababa - Adane Bitew; Amanuel Adane; Abera Abdeta (Scientific Reports, 2023)
Abstract Bloodstream infection coupled with drug resistance in bloodborne bacteria is a major health problem globally. The current study sought to identify the bacterial spectrum, extended-spectrum -lactamase production, and antimicrobial resistance pattern in patients with bloodstream infection. This prospective cross-sectional study was conducted at Arsho Advanced Medical Laboratory, Addis Ababa, Ethiopia from January 2019- until July 2020. Blood collected from patients was inoculated into blood culture bottles and incubated appropriately. Identification, antimicrobial susceptibility testing, and extended-spectrum β-lactamase-production were determined with the VITEK 2 compact system. Of the samples collected, 156 (18.5%) were culture-positive. Klebsiella pneumoniae and Staphylococcus epidermidis were the dominant isolates. In Gram-negative bacteria, the prevalence of drug resistance was the highest against ampicillin (80.8%) and the lowest against imipenem (5.2%). While in Gram-positive bacteria it was the highest against clindamycin and the lowest against vancomycin and daptomycin. The prevalence of multi-drug resistance and extended-spectrum β-lactamase production of Gram-negative bacteria were 41.6% and 34.2%, respectively. The prevalence of bloodstream infection was 18.5%. Serious life-threatening pathogens including S. aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, Escherichia coli, and Enterobacter spp was predominant. The prevalence of multi-drug resistance to both Gram-positive and Gram-negative bacteria and extended-spectrum β-lactamase-production were high but prevalence of carbapenem resistance was low. All these situations call for the establishment of strong infection control strategies, a drug regulatory system, and established antibiotic stewardship in healthcare settings.